Processo de negociação: uma réplica comparativa - SANTANA, Andréia Peruna de (2012)
The mainobjective of this researchis to present anddiscusswhich variablescan interferein the negotiation process, such as individual and cultural differences. This studyisareplicafrom theresearch byJaeger(1999), which wasreplicated in Brazil, through the dissertation:Theinfluence of personality, perceptions andsocial goalsof the behavior andthe resultsof the negotiations, bySantos(2003) andwill be continued, lookingnow,the effectivenessof these simulations, so that, compared to ourrangecanportraymoreagentsand efficiencyof this process. From theliterature review andcomparative studywill be identifiedby the negotiatorcharacteristics and behaviorsthat may contributeto differentiateperceptions andtrading results, in understanding the treatment strategythatmay be subject tosocial interactionsand theirinherentvariables. Thedeal issubjectof great interesttoresearchers, since suchsurveyswereinadequate andonlydevelopedin the contextof the U.S.,presentingfragmented, contradictoryand lowapplicabilitydue to lack ofappropriatemeasuresand criteria, according to Jaeger(1999).Theseresearchers are looking for, mostly, better useof thesedifferences in order togain competitive advantagein the negotiation process.